A case of AML with complex karyotype and chromosomal rearrangement of KMT2A - Habib Moshref Razavi; Agata Minor (Clinical Case Reports, 2024)
Key Clinical Message This is a case of an elderly patient diagnosed with acute myeloid leukemia (AML). While morphological findings, including numerous long, slender, cigar‐shaped Auer rods, suggested AML with t(8;21), cytogenetic and FISH analysis revealed abnormalities in chromosome 11 and the KMT2A (MLL) gene. The patient also exhibited double minutes, typically seen in AML and linked to a complex karyotype and poor prognosis. Correlating morphological findings with molecular genetics and cytogenetics is crucial for accurate diagnosis and treatment.